2010
DOI: 10.1007/s12161-010-9179-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mineral Contents in Tomato Fruits During the Ripening Process After Harvest

Abstract: A comparative study was carried out to evaluate the mineral content of tomato during ripening after harvest. Calcium (Ca), magnesium (Mg), sodium (Na), phosphorus (P), potassium (K), selenium (Se), and zinc (Zn) contents were determined in three of the main tomato types (round, elongated, and cherry) consumed in Portugal. Ca, Mg, Se, and Zn were determined by atomic absorption spectrometry, Na and K by flame photometry, and P by visible spectrometry. No significant variation was found in the Zn, P, Na, and K c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
3
11
2
Order By: Relevance
“…This value was similar to the findings of Anjum et al [27] as ranged between 9.73 to 31.5 mg/100g, Suaréz et al [28] as ranged between 7 to 13 mg/100g. But lower than previous data stated by some authors Nour et al [29] as 13.77 to 32.58 mg/100g and Costa et al [30] as 12 to 20 mg/100g.…”
Section: Content Of Magnesium (Mg)contrasting
confidence: 55%
“…This value was similar to the findings of Anjum et al [27] as ranged between 9.73 to 31.5 mg/100g, Suaréz et al [28] as ranged between 7 to 13 mg/100g. But lower than previous data stated by some authors Nour et al [29] as 13.77 to 32.58 mg/100g and Costa et al [30] as 12 to 20 mg/100g.…”
Section: Content Of Magnesium (Mg)contrasting
confidence: 55%
“…[ 28 ] However, considering that all fruits were collected under the same conditions, the involvement of these minerals in enzymatic reactions during the ripening process could explain a decrease in their abundance. [ 29,30 ] Results found highlight the potential of chontaduro flour to fortify food products for children, elderly, or nursing women.…”
Section: Resultsmentioning
confidence: 99%
“…Gautier et al [ 13 ] reported that the concentration of reducing sugars, carotenes, ascorbate, rutin, and caffeic acid derivatives increased, but titratable acidity, chlorophylls, and chlorogenic acid content decreased during ripening. Costa et al [ 14 ] carried out a comparative study of three different tomato types (round, elongated, and cherry) to evaluate the mineral content in tomato fruits during postharvest ripening. They found no significant variation in Zn, P, Na, and K concentrations, but the content of Ca and Mg tended to decrease and Se content to increase.…”
Section: Introductionmentioning
confidence: 99%